3D interpolation techniques for hydromechanical characteristics in the finite volume method - Lipanov, Alexey Matveevich; Semakin, Artem Nikolaevich (Computational Continuum Mechanics, 2010)
In this paper the interpolation technique of functions with several variables is describe. Three methods of interpolation over arbitrary located points in 3D space (the method based on the determinants, the method based on Taylor’s formula with a remainder, the method based on the Fourier polynomials) are given. For each method the computational formulas are presented. . The examples of calculations for each method are given also. One possible field for application (the final volume method) is specified.